2021
DOI: 10.1177/1545968320981962
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-Induced Movement Therapy Promotes Neural Remodeling and Functional Reorganization by Overcoming Nogo-A/NgR/RhoA/ROCK Signals in Hemiplegic Cerebral Palsy Mice

Abstract: Background. Little is known about the induction of functional and brain structural reorganization in hemiplegic cerebral palsy (HCP) by constraint-induced movement therapy (CIMT). Objective. We aimed to explore the specific molecular mechanism of functional and structural plasticity related to CIMT in HCP. Methods. The mice were divided into a control group and HCP groups with different interventions (unconstraint-induced movement therapy [UNCIMT], CIMT or siRNA-Nogo-A [SN] treatment): the HCP, HCP+UNCIMT, HCP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…CIMT promoted sprouting of the axons and post-stroke motor recovery by blockade of NOGO-A/RhoA/ROCK transduction cascade (Fig. 1) [28].…”
Section: Preclinical Studiesmentioning
confidence: 94%
“…CIMT promoted sprouting of the axons and post-stroke motor recovery by blockade of NOGO-A/RhoA/ROCK transduction cascade (Fig. 1) [28].…”
Section: Preclinical Studiesmentioning
confidence: 94%
“…One of the most popular treatments among clinicians and researchers is constraint-induced movement therapy (CIMT), with an emphasis on constraining the unaffected extremity and coupling task-related practice with the affected upper extremity, and increasing evidence proved the effect of CIMT in children with UCP (Reedman et al, 2017 ; Hoare et al, 2019 ; Ilieva and Ilieva, 2020 ; Simon-Martinez et al, 2020 ). What is more, it was proved that CIMT might promote neural remodeling and thereby improve motor function (Liu et al, 2021 ). However, the findings on the effect of CIMT on improving bimanual coordination are controversial (Reid et al, 2015 ; Hoare et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the positive rate of SNPs in CP is 14–19% [ 16 ], there are more potential SNPs variants that need to be further discovered and studied. Our team's previous studies found that neurite outgrowth inhibitor-A (Nogo-A) plays a vital role in the nerve remodeling and functional recovery of CP mice [ 31 ], but so far, there is no research to explore the role of Nogo-A gene in the development of CP.…”
Section: Introductionmentioning
confidence: 99%